From trash to treasure: the recycling of glass in Roman and Early Medieval period Britain - Sainsbury, V (2019)
The main aim of this thesis is twofold; first to asses the ability of material studies to identify and quantify recycling in ancient glass, and then to compare the nature and extent of recycling of glass in the first to fourth centuries in Britain, Roman Britain, to the following Early Medieval period, fifth to eighth centuries.